THE EFFECT OF SIMRS IMPLEMENTATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT RSIA MUHAMMADIYAH PROBOLINGGO - Dyan Angesti; Sulistiowati; Januar Wibowo; Moh. Arifin (Universitas PGRI Adi Buana, 2026)
This study aims to analyze the effect of SIMRS implementation and organizational culture on the performance of employees at RSIA Muhammadiyah Probolinggo. It is expected to provide an empirical description and basis for developing strategies to improve human resource quality and SIMRS effectiveness in order to support optimal health services. The research method used is quantitative with a cross-sectional study approach. The population consisted of 166 SIMRS users, while the sample consisted of 92 people, but only 89 people met the requirements. The SIMRS application implementation variable was measured based on five main dimensions, including: Information Quality, System Quality, Service Quality, User Satisfaction, Net Benefit, and Organizational Culture Variables. Data analysis used path analysis with Smart PLS and contingency coefficient tests as an alternative to influence tests. The results of the bootstrapping analysis showed that most of the variables tested did not have a significant effect on user satisfaction, with only the Cultural Norm variable on User Satisfaction showing a significant effect. User satisfaction with SIMRS has not contributed directly to improved performance. Organizational culture has a positive and significant effect on SIMRS user satisfaction. The conclusion of this study is that the implementation of SIMRS has not had a significant effect on employee performance. Organizational culture has a positive and significant effect on SIMRS user satisfaction and indirectly plays a role in encouraging employee performance. Performance improvement is directed not only at aspects of information technology, but also at strengthening organizational culture and increasing human resource capacity.